A survey about the establishment of the Libyan Journal of Dentistry (LJD) - Mohamed, Khadiga; Mohamed, Mahfud; Saod, Loai; Saoud, Tarek (Libyan Journal of Dentistry, 2018)
Aim: This questionnaire was performed to introduce LJD and to know the feedback of the readers about the firstpublished issue. Methods: About 75 copies of the questionnaire were distributed. Only 61 who were answered and returned. The collected answered questionnaire were tabled and analyzed. Results: About 72% of the respondents have heard about LJD, about 95% of them were believed in the importance of creating a LJD at this time, and 16% of them have accessed to our journal web site.